Analyzing Foundations of Imposing a Monetary Penalty on Parties to a Criminal Proceeding - SAKHARBAY, Arman; KALIYEV, Askar Kadyrovich; BAIKOMUROVA, Moldir Saparbekkyzy (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The research analyzes the possible application and effectiveness of a monetary penalty as one of the most useful sanctions to maintain the established order of criminal justice, as well as develops constructive proposals to improve the criminal procedure legislation based on the conducted survey. To this end, the authors of the article have studied the criminal procedure legislation of Kazakhstan and legislation on administrative offenses, considered scientific opinions presented in numerous publications on relevant topics and conducted a comparative analysis of regulatory systems in Kazakhstan, Germany, Austria, the USA and the UK. As a result, the authors have established that one of the main reasons hindering the adequate implementation of criminal justice is the violation of obligations to participate in criminal proceedings by persons named in the Criminal Procedure Code of Kazakhstan. To maintain procedural discipline, the court is provided with ample opportunities in the form of coercive measures, including a monetary penalty. The authors have investigated the legal nature of a monetary penalty and compared it with administrative fines. The authors have considered grounds and application procedures for this sanction in the criminal procedure legislation of Kazakhstan and some foreign legal systems. The authors have determined the problems of its implementation caused by the slovenly legislation of a monetary penalty that impedes law enforcement activity. A comprehensive analysis allows developing proposals for improving the use of monetary penalties as measures of coercion for criminal cases heard in the court. If these proposals are enshrined in the existing regulatory framework and put into practice, they will strengthen the discipline of parties to criminal proceedings, ensure the strict observance of criminal proceedings and increase their general effectiveness. Due to its conclusions and proposals, the article demonstrates the novelty of the conducted research, the authors' original approach to the analysis of information and innovative ways to improve the existing legislative framework.